No signs of inbreeding despite long-term isolation and habitat fragmentation in the critically endangered Montseny brook newt (Calotriton arnoldi) - Valbuena-Ureña, E (Heredity (Edinb), 2017)
Endemic species with restricted geographic ranges potentially suffer the highest risk of extinction. If these species are further fragmented into genetically isolated subpopulations, the risk of extinction is elevated. Habitat fragmentation is generally considered to have negative effects on species survival, despite some evidence for neutral or even positive effects. Typically, non-negative effects are ignored by conservation biology. The Montseny brook newt (Calotriton arnoldi) has one of the smallest distribution ranges of any European amphibian (8 km(2)) and is considered critically endangered by the International Union for Conservation of Nature. Here we apply molecular markers to analyze its population structure and find that habitat fragmentation owing to a natural barrier has resulted in strong genetic division of populations into two sectors, with no detectable migration between sites. Although effective population size estimates suggest low values for all populations, we found low levels of inbreeding and relatedness between individuals within populations. Moreover, C. arnoldi displays similar levels of genetic diversity to its sister species Calotriton asper, from which it separated around 1.5 million years ago and which has a much larger distribution range. Our extensive study shows that natural habitat fragmentation does not result in negative genetic effects, such as the loss of genetic diversity and inbreeding on an evolutionary timescale. We hypothesize that species in such conditions may evolve strategies (for example, special mating preferences) to mitigate the effects of small population sizes. However, it should be stressed that the influence of natural habitat fragmentation on an evolutionary timescale should not be conflated with anthropogenic habitat loss or degradation when considering conservation strategies.